Pengaruh Sistem Informasi Manufaktur Terhadap Motivasi Kerja Karyawan Pada Pt Jp Technology - Muhammat Rasid Ridho (Universitas Putera Batam, 2014)
Manufacturing Information System is needed by the production management information used for planning, organizing, controlling the production. Inputting data using MS Excel is still less than the maximum in assisting in generating the required information managers or others in need. The management wants mounted display report output in the large LCD monitor will be placed in strategic so that all employees can see it. This is so that the employees are motivated because look yield comparison with other employees. This research was conducted in the form of questionnaires that assess the activity of manufacturing information system quality and employee motivation itself. IT staff are expected to be easier in the continuing development of a more complex system.